Identifying the Main Motivations to Visit Salt Mines: Do Socio-Demographic Variables Matter? - CHIRICHEŞ, Mihaela Gabriela; EGRESI, István (Studia Universitatis Babeș-Bolyai Geographia, 2024)
Identifying the Main Motivations to Visit Salt Mines: Do Socio-Demographic Variables Matter? Salt has been extracted from mines in Europe for thousands of years. More recently, some of these salt mines reinvented themselves as new tourism objectives attracting hundreds of thousands and even millions of visitors each year. This research aims to investigate the main reasons tourists visit a former salt mine, focusing on Turda Salt Mine, in Romania, as a case study. The study found that the main motivations for visiting the former salt mine were leisure/relaxation, learning, adventure, to try something new and to escape the daily routine whereas participation in various cultural/religious and sport events as well as socialization with like-minded people were considered the least important motivations. The results also show that some socio-demographic factors could influence motivation to visit a salt mine. The findings of this research have a number of practical implications for the marketing and management of salt mines which are outlined at the end of the paper.